Translation and validation of traditional Chinese version of the pediatric eating assessment Tool-10 - Sz-Ting Wang; Kun-Tai Kang; Wen-Chin Weng; Pin-Hung Lu; Chi-Fen Chang; Yuh-Yu Lin; Yu-Chen Lee; Chen-Yu Chen; Jing-Chun Song; Wei-Chung Hsu (Journal of the Formosan Medical Association)
Background/Purpose: The Pediatric Eating Assessment Tool-10 (Pedi-EAT-10) is a caregiver-administrated subjective questionnaire for evaluating swallowing and feeding disorders among children. This study translated the Pedi-EAT-10 into Traditional Chinese and tested the translated version's reliability and validity. Methods: Pedi-EAT-10 was translated into Traditional Chinese by experts and finalized after discussion and testing. A total of 168 participants, consisting of 32 children with dysphagia from a tertiary medical center and 136 healthy controls from its Children Care Center for Employees, were recruited. All participants were assessed by an otolaryngologist and speech-language pathologist. The reliability, validity, and efficacy of the translated Pedi-EAT-10 were analyzed to ensure it could be used to identify pediatric dysphagia and feeding problems. Results: The Traditional Chinese version of the Pedi-EAT-10 had significant clinical discriminative validity between the dysphagia group and the control group (total score = 9.6 vs. 2.6, P < 0.001), acceptable test–retest reliability (intraclass correlation = 0.63), and excellent internal consistency (Cronbach's α = 0.91 for the entire cohort). The overall performance of the test for distinguishing children with dysphagia from normal controls was acceptable, and the area under the curve was 74.8% (sensitivity = 71.9%; specificity = 69.9%). The optimal cutoff score was ≥3 on the Youdex index. Conclusion: The Traditional Chinese version of the Pedi-EAT-10 has fair reliability and validity and can be quickly and easily completed by caregivers. The translated Ped-EAT-10 can be used as a first-line tool for assessing the need for further referral and instrumental examination.